Evaluating the M6 learning model and realistic mathematics education (RME) approach in enhancing critical thinking skills in mathematics: A focus on students’ logical-mathematical intelligence - Susandi, Ardi Dwi; Sudirman, Sudirman; Khoiriyah, Binti (Al-Jabar: Jurnal Pendidikan Matematika, 2024)
Background: Critical thinking skills are essential in the 21st century; however, Indonesian students often show low critical thinking abilities in mathematics. This issue arises partly from limited use of instructional methods that foster critical thinking among junior high school students.Aim: This study aims to assess the effectiveness of the M6 learning model and Realistic Mathematics Education (RME) in enhancing students' critical thinking abilities in mathematics, considering their levels of logical-mathematical intelligence.Method: A quasi-experimental design was employed with a sample of 318 seventh-grade students from State Middle Schools in Cirebon Regency in the 2023/2024 academic year. Stratified cluster random sampling produced three groups: 107 students in the first experimental group, 105 in the second, and 106 in the control group. Instruments included a critical mathematical thinking skills test and a logical-mathematical intelligence test, with hypothesis testing conducted using two-way analysis of variance with unequal cells.Results: The analysis revealed significant differences in students' critical thinking abilities based on the learning model and logical-mathematical intelligence levels, with notable interactions between these variables.Conclusion: The study concludes that the M6 and RME learning models influence critical mathematical thinking skills differently across logical-mathematical intelligence categories. These findings underscore the importance of aligning instructional models with students' intelligence profiles to optimize learning outcomes in critical thinking.